Analysis of The Influence of Inclusive Education Policies and Community Empowerment on Islamic Religious Education at Madrasah Aliyah Al-Aziziyah - Fattah, Ammar Abdul; Ahyar, Ahyar; Fahrurrozi, Fahrurrozi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
The aims of this research is to explain the influence of inclusive education policies and community empowerment on Islamic religious education at Madrasah Aliyah Al-Aziziyah. This research uses a quantitative type with an analytical design. This research wants to see whether there is an influence or not on inclusive education policies (X1) and community empowerment (X2) towards Islamic religious education (Y) at Madrasah Aliyah Al-Aziziyah. The population of this study were all teachers and people related to Madrasah Aliyah Al-Aziziyah and the sample was 30 people. The sampling technique used is random sampling. Data collection techniques through observation with questionnaire instruments for inclusive education policies and community empowerment regarding Islamic religious education. The data analysis technique uses the one-way Anova test. The research results show that there is an influence of inclusive education policies and community empowerment on Islamic religious education at Madrasah Aliyah Al-Aziziyah as seen from the significant value obtained in the one-way Anova test which is greater than 0.05 and Islamic religious education has an influence on inclusive education and community empowerment.